The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1021/ef0100606
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Thermal Processing of Methane to Produce Hydrogen and Syngas

Abstract: A solar-thermal aerosol flow reactor has been constructed, installed, and tested with the High-Flux Solar Furnace (HFSF) at the National Renewable Energy Laboratory (NREL). Experiments were successfully carried out for the dissociation of methane to produce hydrogen and carbon black and for the dry reforming of methane with carbon dioxide to form syngas (hydrogen and carbon monoxide). Approximately 90% dissociation of methane was achieved in a 25-mm diameter quartz reaction tube illuminated with a solar flux o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 16 publications
(15 reference statements)
0
21
0
Order By: Relevance
“…In order to achieve a net CO 2 conversion, the heat of reaction must not be created by burning fossil fuels. Instead solar-thermal reactors are an interesting development [24] and could be used in the future. Aside from environmental aspects, methane dry reforming is of general interest to the chemical industry because it delivers a lower H 2 =CO ratio than steam reforming which is desirable, e.g.…”
Section: Dry Reformingmentioning
confidence: 99%
“…In order to achieve a net CO 2 conversion, the heat of reaction must not be created by burning fossil fuels. Instead solar-thermal reactors are an interesting development [24] and could be used in the future. Aside from environmental aspects, methane dry reforming is of general interest to the chemical industry because it delivers a lower H 2 =CO ratio than steam reforming which is desirable, e.g.…”
Section: Dry Reformingmentioning
confidence: 99%
“…In the solar field, very high sunlight concentration factors (about 3000) are needed to reach temperatures over 1500 K [3,[22][23][24][25][26]. There are already some designs and experimental set-ups that could be useful for long-term generation of H 2 [27].…”
Section: Introductionmentioning
confidence: 99%
“…1, that was obtained from Gemini software [7] (software for thermodynamic equilibrium calculation developed by Thermodata), shows that methane decomposition is complete at about 1300 K. However, the reaction is not kinetically favorable [8,9], and a higher temperature is required to obtain high methane to hydrogen conversion rates and high-quality CB. Dahl et al [10] obtained exactly the same equilibrium products than that shown in Fig. 1, and they found that trace products at 1500 K include acetylene, ethylene, butylene, propylene, ethane at quantities less than 1 × 10 −3 moles for 1 mole of methane fed.…”
Section: Introductionmentioning
confidence: 55%
“…The reaction is kinetically hindered and the residence time (t r ) of the reactant in the high-temperature reacting zone (for a nozzle type b, i.e. 10 mm diameter and 10 mm cavity length, and a global flow rate of 1.1 L n / min, t r is about 40 ms at normal conditions and 8 ms at 1500 K, 1 atm) is not high enough to reach significant conversion [10]. Tables 2 and 3 list the results obtained with a 2 m-diameter concentrator and the corresponding operating conditions.…”
Section: Preliminary Experiments With a 15 M-diameter Solar Concentrmentioning
confidence: 99%
See 1 more Smart Citation